2015
DOI: 10.1099/mic.0.000121
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of human epithelial cell lines by Corynebacterium ulcerans from human and animal sources

Abstract: Corynebacterium ulcerans is an emerging pathogen transmitted by a zoonotic pathway to humans. Despite rising numbers of infections and potentially fatal outcomes, data on the colonization of the human host are lacking up to now. In this study, adhesion of two C. ulcerans isolates to human epithelial cells, invasion of host cells and the function of two putative virulence factors with respect to these processes were investigated. C. ulcerans strains BR-AD22 and 809 were able to adhere to Detroit562 and HeLa cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
(41 reference statements)
3
11
0
Order By: Relevance
“…The more aggressive behavior of C. ulcerans 809 toward epithelial cells might be due to the additional Shiga-like toxin this strain carries. 27 Taken together, the observations made in this study hint to the existence of more than one active mechanism of C. ulcerans to cope with macrophage function. In line with this idea, initial sequencing of strains 809 and BR-AD22 25 as well as next generation sequencing of 9 C. ulcerans isolates 8 revealed a number of different virulence factors, which might influence survival of this pathogen besides the Shiga-like toxin of strain 809 as well as PLD and DIP0733 homolog CULC22_00609 of BR-AD22.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The more aggressive behavior of C. ulcerans 809 toward epithelial cells might be due to the additional Shiga-like toxin this strain carries. 27 Taken together, the observations made in this study hint to the existence of more than one active mechanism of C. ulcerans to cope with macrophage function. In line with this idea, initial sequencing of strains 809 and BR-AD22 25 as well as next generation sequencing of 9 C. ulcerans isolates 8 revealed a number of different virulence factors, which might influence survival of this pathogen besides the Shiga-like toxin of strain 809 as well as PLD and DIP0733 homolog CULC22_00609 of BR-AD22.…”
Section: Discussionsupporting
confidence: 62%
“…34 BR-AD22 strains carrying a pld and CULC22_00609 gene disruption, respectively, were generated and designated ELHA1 and ELHA3. 27,35 When cells were infected with these mutant strains and LDH release was measured, at MOI 1 strain ELHA1 showed 51 § 16 % and ELHA3 34 § 13 % cytotoxicity compared to the wild type, indicating a multifactorial mechanism of macrophage damage, which has to be analyzed in more detail in future. A complex interaction is also indicated by the fact that the defect of mutant strains observed at MOI 1 could be overcome by higher MOIs (data not shown).…”
Section: Response Of Human Macrophages To C Ulcerans Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a recent study showed that a corresponding mutant for the DIP0733 homolog in C. ulcerans (CULC22_00609) showed no effect on adhesion to and invasion into epithelial cells [35]. Remarkably, this data corroborates with our study, as the coiled-coil domain of DIP0733 was predicted to be present only in C. diphtheriae and C. pseudotuberculosis and absent in C. ulcerans.…”
Section: Discussionsupporting
confidence: 92%
“…Whilst a dramatic break-down of transepithelial resistance was not observed for most of the C. diphtheriae strains tested by Ott and co-workers, C. diphtheriae DSM43989 showed the most severe effect after 3 h of infection [17], which was similarly demonstrated by the CDC-E8392 wild-type strain in this study. Conversely, other strain specific proteins and cellular niche factors may be involved in this process as similar effects were described for C. ulcerans 809 [35]. …”
Section: Discussionmentioning
confidence: 71%